Variability in the severity of colonic disease in familial adenomatous polyposis results from differences in tumour initiation rather than progression and depends relatively little on patient age. Issue 4 (1st October 2001) - Crabtree, M D; Tomlinson, I P M; Talbot, I C; Phillips, R K S
Abstract : INTRODUCTION: As large scale genetic analysis becomes increasingly efficient, attention is turning to problems arising from inaccurate measurement of the phenotype. We have investigated the underlying basis of variation in disease severity in the large intestine of familial adenomatous polyposis (FAP) patients. The development of objective and reproducible measures may have future use in genetic studies, such as analysis of modifier genes. METHODS: We examined the ratio of adenomas to crypts from microscopic slides taken from all parts of the colon of 44 resected FAP specimens. These findings were compared with a carefully reported macroscopic polyp count. Age dependency of adenoma counts (in the period around colectomy) was also analysed. RESULTS: The adenoma:crypt ratio strongly correlated with reported macroscopic polyp count ( r =0.82, p<0.001) with no significant residual variation. Polyp density measured using the adenoma: crypt ratio did not vary significantly within an individual colon. Apparent visible variation in polyp density within any colon was not found at the microscopic level. There was no detectable age related increase in macroscopic adenoma count between siblings over the age range at which colectomies were performed. DISCUSSION: The severity of colonic polyposis in FAP can be determined accurately by counting the adenoma:crypt ratio in sections derived from stored tissue blocks. Variation between patients—dependent on APC genotype and, probably, modifier genes—is manifest at both the microscopic and macroscopic levels. Thus variation in disease severity is more likely to result from different rates of tumour initiation than from differences in progression of microadenomas to macroscopic tumours. The absence of a detectable relationship between adenoma number and age (over the range studied) suggests that most tumours may be initiated relatively early in the patient's life, perhaps at a time of particular susceptibility.